Supernatural sources of martial power: a cross-cultural investigation - Jared Miracle (Revista de Artes Marciales Asiáticas, 2014)
This paper utilizes a cross-cultural comparison model of cultural inquiry to approach the question of whether or not there are generalizable trends in the intersection of fighting arts and cultural conceptions of the supernatural. The methods are outlined and background presented to explain how the investigation was undertaken. Sources are limited to the eighteenth and nineteenth centuries and bounded geographically. The regions included are the Japanese archipelago, China, the Afro-Atlantic, the Great Plains of North America, and the Indian subcontinent. The five regions were chosen at random and do not represent an attempt to be comprehensive. Explanation of the evidence is followed by a comparative discussion. While further study is required, the most apparent tentative conclusion is that cultural understanding of supernatural intervention combines with the martial arts in cases where not only physical, but socio-political power is sought in asymmetrical conflict.